Y(t) = 22,22 - 23,97*exp(-0,3t) - 5,556*exp(-1,5t) + 9,01*cos(0,866t+0,6251)
*exp(-1,5t) for t >= 0
la respuesta es
p1.a =
-4,8000000 1 0 0
-8,8500000 0 1 0
-6,7500000 0 0 1
-1,3500000 0 0 0
p1.b =
0
1
4
3
p1.c =
1 0 0 0
p1.d = 0
p2.a =
0 1 0 0
0 0 1 0
0 0 0 1
-1,3500000 -6,7500000 -8,8500000 -4,8000000
p2.b =
0
0
0
1
p2.c =
3 4 1 0
p2.d = 0
1s^2 +4s +3
Gc(s) = ———————————————
s^4 +4,8s^3 +8,85s^2 +6,75s +1,35
s^2 +4s +3
G(s) = ————————————————
s^4 +4,8s^3 +8,85s^2 +6,75s +1,35
La grafica de la respuesta en el tiempo es:
No hay comentarios:
Publicar un comentario